2016
DOI: 10.1097/pcc.0000000000000571
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin to Detect Suspected Bacterial Infections in the PICU

Abstract: Procalcitonin levels were higher in children with documented confirmed bacterial infection as compared with those with low suspicion of infection. However, neither single nor serial procalcitonin measurements were able to predict the presence or absence of confirmed bacterial infection with enough certainty to be clinically useful as to recommend initiating or withholding antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…19 Although that study was performed prospectively, only 33% (n=107) of eligible patients were included in the primary analysis, and most of the patients with incorrect PCT classification were false-positive rather than false-negative results (ie, PCT was more useful to “rule-out” rather than “rule-in” bacterial infection). Also, patients were categorized without regard to shock by Mandell et al and 25.7% of patients without bacterial infection required inotropic support.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Although that study was performed prospectively, only 33% (n=107) of eligible patients were included in the primary analysis, and most of the patients with incorrect PCT classification were false-positive rather than false-negative results (ie, PCT was more useful to “rule-out” rather than “rule-in” bacterial infection). Also, patients were categorized without regard to shock by Mandell et al and 25.7% of patients without bacterial infection required inotropic support.…”
Section: Discussionmentioning
confidence: 99%
“…Prior pediatric studies have reported mixed results, and few studies have specifically examined the use of PCT in the pediatric intensive care unit (PICU). 1619 In some cases, PCT has yielded superior test characteristics than routinely used laboratory tests, such as measurement of C-reactive protein (CRP), white blood cell count (WBC), and percentage immature neutrophils (% Imm), but the optimal cut-point reported for PCT to guide clinical decision-making remains highly variable across studies. 2024 One common limitation of prior studies has been the relatively small sample size of subjects analyzed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Serial PCT concentrations have been recently studied (by Mandell et al 15 in 2016) in the pediatric population in regard to sepsis. They suggested that patients with confirmed viral infections in the absence of bacterial infections demonstrated rising PCT concentrations and concluded that the trend in PCT concentrations could not accurately be used to predict the presence or absence of bacterial infection.…”
Section: Bacteroides Tectum 1 (3)mentioning
confidence: 99%
“…13 In a prospective, observational study of 144 critically ill children with suspected bacterial infections, PCT levels were higher in those with confirmed bacterial infections as compared with those with low suspicion for bacterial infection. 14 However, no large-scale studies of the diagnostic accuracy of serum PCT for bacteremia alone have been performed in febrile, critically ill, pediatric patients.…”
Section: Introductionmentioning
confidence: 99%